2017
DOI: 10.3892/or.2017.5448
|View full text |Cite
|
Sign up to set email alerts
|

miR-30a radiosensitizes non-small cell lung cancer by targeting ATF1 that is involved in the phosphorylation of ATM

Abstract: Increasing number of studies report that microRNAs play important roles in radiosensitization. miR-30a has been proved to perform many functions in the development and treatment of cancer, and it is downregulated in non-small cell lung cancer (NSCLC) tissues and cells. This study was conducted to understand if miR-30a plays a role in the radiosensitivity of NSCLC cells. Radiosensitivity was examed by colony survival assay and tumor volume changing in vitro and in vivo, respectively. Bioinformatic analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…miR-502e was found to serve as a tumor suppressor and inhibit NSCLC cell growth, invasion and migration by targeting Zbtb7a partly depending on the Wnt signaling pathway (13). However, miR-30a reduced radiation-induced G2/M cell cycle arrest and may also affect radiation-induced apoptosis by targeting ATF1 (14). This accumulating evidence shows that miRNAs are promising biomarkers and therapeutic targets in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…miR-502e was found to serve as a tumor suppressor and inhibit NSCLC cell growth, invasion and migration by targeting Zbtb7a partly depending on the Wnt signaling pathway (13). However, miR-30a reduced radiation-induced G2/M cell cycle arrest and may also affect radiation-induced apoptosis by targeting ATF1 (14). This accumulating evidence shows that miRNAs are promising biomarkers and therapeutic targets in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The recent identification of a novel class of non-proteincoding miRNA, with no open reading frame, has confirmed that the genomic complexity of cancer far exceeds original expectations (15). miRNAs are a type of small endogenous non-coding RNA with no open reading frame, which are 20-25 nucleotides in length.…”
Section: Microrna-145 Inhibits Migration and Induces Apoptosis In Hummentioning
confidence: 99%
“…Accumulating evidences disclose that several miRNAs act as important biomarkers for the diagnosis and prognosis of various cancers, such as NSCLC, pancreatic cancer and colorectal cancer (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%